Flipped Classroom Mobile Learning Model and Its Application to Enhance Digital Intelligence Quotient among Secondary Students - Phumeechanya, Noppadon (International Journal of Interactive Mobile Technologies (iJIM), 2024)
Digital intelligence quotient (DQ) is an essential skill for becoming a digital citizen. In Thailand, the development of DQ is a key policy initiative for youth development. Using mobile applications in a flipped classroom (FC) setting enhances learning outcomes and fosters the development of critical skills. This paper proposes a mobile application integrated with a FC model to improve secondary education students’ DQ. The study utilized an experimental research design with a one-group pretest-posttest approach to compare students’ DQ, analyzed using a paired sample t-test, and assessed student satisfaction. The sample consisted of 60 lower secondary school students under Thailand’s Nakhon Pathom Secondary Education Service Area Office. The research findings are as follows: 1) The developed learning model was rated as highly appropriate; 2) The content and technical quality of the FC mobile application was rated very good; 3) Students’ DQ significantly improved after using the application, with a statistical significance level of 0.05. Among the eight sub-skills, screen time management showed the highest improvement; and 4) Student satisfaction with the learning model was at the highest level. Based on these findings, the developed model can enhance students’ DQ and is adaptable for other audiences requiring digital navigation skills, making the results relevant to broader educational objectives beyond traditional coursework.